Storytelling Method in Learning Process – Thematic Analysis - Salix (West Science Business and Management, 2024)
Learning is often perceived as an unpleasant and compulsory activity, limiting its true purpose to obtaining certifications rather than fostering understanding. This study explores storytelling as an effective pedagogical approach to enhance student engagement, comprehension, and critical thinking. Storytelling stimulates curiosity and allows learners to connect with the material on a personal level, making information more meaningful. Research suggests that storytelling improves cognitive processes by promoting visualization, structuring knowledge, and fostering cause-and-effect reasoning. The literature review highlights that storytelling is a powerful teaching method, offering structured content delivery, emotional engagement, and real-world application. By integrating storytelling with visualization, educators can create immersive learning experiences that cater to various learning styles. This method enhances memory retention, encourages inquiry-based learning, and supports knowledge construction. The study employs thematic analysis to identify key storytelling elements contributing to effective learning. Findings suggest that structured storytelling, engaging narrative delivery, and visualization techniques significantly enhance student learning outcomes. The integration of storytelling in pedagogy fosters deeper comprehension, analytical skills, and creativity. This study provides a framework for implementing storytelling in education, emphasizing its role in making learning an interactive and meaningful process.